Pengaruh Komite Audit dan Karakteristik Keuangan terhadap Financial Distress - Annisa Zabrina (Jurnal Riset Perbankan Manajemen dan Akuntansi, 2021)
The purpose of this research is to analyze the effect of audit committee and financial characteristics on the financial distress. The sampling technique using purposive sampling from manufacturing sector companies listed on Indonesia Stock Exchange (IDX). The type of data is secondary data from IDX in the form of financial statements in the period of 2017-2018. Based on the sample selection from 186 companies, there are 250 samples were used in this research. Both the dependent variable financial distress and the independent variables audit committee, size, leverage, and growth are measured by the ratio scale. The data were processed and analyzed using multiple linear regression analysis by using SPSS. The result of this research shows that leverage has a positive effect on financial distress, audit committee has a negative effect on financial distress, while firm size and firm growth have no effect on financial distress. Keywords: Financial distress, audit committee, size, leverage, firm growth